Analysis of Figurative Language and Translation Strategies in Picture Me Gone - Warminingsih; Syamsurrijal, Syamsurrijal (CV Insan Kreasi Media, 2025)
This study is motivated by the increasing reading interest in Indonesia, as reflected in national literacy data and the rising availability of translated English novels that enrich Indonesian literary culture and promote cross-cultural understanding. Figurative language is a crucial element in novels, enhancing emotional depth and narrative style, but its translation poses challenges due to cultural and linguistic differences. This research examines the use of figurative language in Meg Rosoff’s Picture Me Gone and the techniques used to translate these expressions into Indonesian. Employing a mixed qualitative and quantitative method, the study identifies 73 figurative expressions in the novel. Similes appear 23 times (32%), metaphors 18 times (25%), idioms 12 times (16%), personifications 10 times (14%), hyperboles 8 times (11%), while onomatopoeia and oxymoron each appear once (1%). Guided by Peter Newmark’s translation theory, six translation techniques were identified. Literal translation is the most dominant, found in 39 cases (53%), followed by modulation in 18 cases (25%). Reduction and descriptive equivalent are each applied in 6 cases (8%), paraphrase in 3 cases (4%), and transposition in 1 case (1%). The study highlights the difficulties translators face in preserving meaning, tone, and cultural nuances in figurative language. To address these challenges, translators adapt their strategies to maintain both fidelity to the original and naturalness in the target language. This research contributes to a deeper understanding of figurative language translation in literary texts and offers practical insights for translators, students, and literature enthusiasts.